The influence of music education combined with sports psychology on students’ anxiety - Rong Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The mental health of college students has become a topic of public discourse and is one of the most pressing issues confronting colleges and universities on the path to survival and development. This study aims to determine the effect of music education and sports psychology on student anxiety. This eight-week study examined the students of a college of physical education using SAS and a questionnaire. Free recovery, sports prescription recovery, group psychological counseling recovery, and sports prescription plus group psychological counseling recovery were implemented as intervention measures. 37% had anxiety symptoms, with most students in social athletics classes suffering from anxiety disorders. There is a significant difference between the proportion of male and female anxiety sufferers. Before and after the intervention, the contents of serum 5-hydroxytryptamine (5-HT), brain-derived neurotrophic factor (BNDF), and plasma cortisol (COR) were measured; after the intervention, the contents of 5-HT, BNDF, and COR were significantly increased (P0.05 or P0.01) in all groups except the free recovery group. The anxiety level of apprehensive college students can be reduced using the intervention. These findings are novel and contribute significantly to the existing body of knowledge. The study suggests some prospective research directions for scholars to consider.